Investigation of 3D mechanical structure of campaniform sensillum as an inspiration for biomedical sensing device [electronic resource] - Raziah Esa, 1988- author (2014)
Thesis (Sarjana Kejuruteraan (Bioperubatan)) - Universiti Teknologi Malaysia, 2014